Demonstration of a mid-infrared cavity enhanced absorption spectrometer for breath acetone detection. - Ciaffoni, L; Hancock, G; Harrison, J; van Helden, J; Langley, C; Peverall, R; Ritchie, G; Wood, S (2013)
A high-resolution absorption spectrum of gaseous acetone near 8.2 μm has been taken using both Fourier transform and quantum cascade laser (QCL)-based infrared spectrometers. Absolute absorption cross sections within the 1215-1222 cm(-1) range have been determined, and the spectral window around 1216.5 cm(-1) (σ = 3.4 × 10(-19) cm(2) molecule(-1)) has been chosen for monitoring trace acetone in exhaled breath. Acetone at sub parts-per-million (ppm) levels has been measured in a breath sample with a precision of 0.17 ppm (1σ) by utilizing a cavity enhanced absorption spectrometer constructed from the QCL source and a linear, low-volume, optical cavity. The use of a water vapor trap ensured the accuracy of the results, which have been corroborated by mass spectrometric measurements.